2008
DOI: 10.1128/jvi.00819-08
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin KIF4 Regulates Intracellular Trafficking and Stability of the Human Immunodeficiency Virus Type 1 Gag Polyprotein

Abstract: Retroviral Gag proteins are synthesized as soluble, myristoylated precursors that traffic to the plasma membrane and promote viral particle production. The intracellular transport of human immunodeficiency virus type 1 (HIV-1) Gag to the plasma membrane remains poorly understood, and cellular motor proteins responsible for Gag movement are not known. Here we show that disrupting the function of KIF4, a kinesin family member, slowed temporal progression of Gag through its trafficking intermediates and inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 60 publications
(84 reference statements)
9
73
0
Order By: Relevance
“…This is not without precedence. For example, Resh and colleagues showed that Gag transits through intracellular bodies before being trafficked to the plasma membrane (Martinez et al, 2008), and the selective knockdown of cellular RNA-binding proteins blocks HIV-1 RNA transport at distinct intracellular loci (Levesque et al, 2006). This type of selectivity of a Staufen RNP was also found in Drosophila in the SpongeBody (Snee and Macdonald, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…This is not without precedence. For example, Resh and colleagues showed that Gag transits through intracellular bodies before being trafficked to the plasma membrane (Martinez et al, 2008), and the selective knockdown of cellular RNA-binding proteins blocks HIV-1 RNA transport at distinct intracellular loci (Levesque et al, 2006). This type of selectivity of a Staufen RNP was also found in Drosophila in the SpongeBody (Snee and Macdonald, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…Unlike synaptic vesicles, dense core vesicles and UNC-6/netrin [which were shown to accumulate in the cell body and dendrites of unc-104 mutants (Asakura et al, 2010;Hall and Hedgecock, 1991;Nonet, 1999;Ou et al, 2010;Zahn et al, 2004)], TIR-1 was not detected in the AWC cell body or dendrites in unc-104 mutants. These results suggest that unc-104 may be required for the stability of TIR-1 protein, similar to the function of kinesin KIF4 in regulating intracellular trafficking and stability of HIV-1 Gag polyprotein (Martinez et al, 2008). To rule out the possibility that the odr-3 promoter is downregulated in unc-104(e1265) mutants, the expression level of odr-3p::GFP was examined in wild-type and unc-104(e1265) mutants.…”
Section: Research Articlementioning
confidence: 99%
“…KIF4A has been reported to participate in a variety of cell processes, including intracellular trafficking of HIV gag and integrin-β 1 (Martinez et al, 2008;Willemsen et al, 2014), mitotic progression (Zhu and Jiang, 2005;Wandke et al, 2012), DNA damage response (Wu et al, 2008) and brain neuron development (Midorikawa et al, 2006). It has been also reported that KIF4A was upregulated in lung cancer and could serve as a prognostic biomarker and therapeutic target for lung cancer (Taniwaki et al, 2007;Zhu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%